MENGANALISIS UNSUR INTRINSIK CERPEN “KATASTROPA” KARYA HAN GAGAS SEBAGAI UPAYA MENYEDIAKAN BAHAN AJAR MENULIS TEKS CERPEN - Dian Maryanti; Rena Sujiana; Wikanengsih Wikanengsih (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
The objective of this research was (1) to describe the intrinsic substance from the short story "Katastropa" written by Han Gagas. (2) to know the ability from the student of MA Tanjung Jaya in analyzing intrinsic substance from short story as an effort to supply material for teaching short story text. the analysis was doing toward the intrinsic substances which exist in the short story Katastropa written by Han Gagas such as character, plot, background, then the theme and the commision. the sample that used in this research were 20 students. descriptive qualitative was used as the type of the research. the method which used in collecting data were obtained from student sheet. the data then analyzed based on intrinsic substance in short story. from the result of the analysis, the researcher could make a conclusion that the intrinsic substances in story Katastropa written by Han Gagas can be concluded as an effort to supply material for teaching writing short story text.